2013
DOI: 10.4067/s0301-732x2013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Reporte del primer hallazgo de puma (Puma concolor puma) infectado con Trichinella sp. en Chile

Abstract: Reporte del primer hallazgo de puma (Puma concolor puma) infectado con Trichinella sp. en Chile #

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
9
1
1
Order By: Relevance
“…The density of larvae in the cougar in this report was low in comparison with that of the previous report from Chile (Hidalgo, et al, , and similar to that of a report of T. spiralis in cougars in Argentina (Ribicich, et al, 2010, 1 lpg). The cougar in this work showed a better overall condition than the one described by Hidalgo et al (2013). Although the disease has been reported in animals (Rice, et al, 1990;Ribicich, et al, 2007;Bowman, 2009;Ribicich, et al, 2013), the infecting dose necessary for clinical signs is usually high, resulting in higher larvae densities than that observed in this report.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…The density of larvae in the cougar in this report was low in comparison with that of the previous report from Chile (Hidalgo, et al, , and similar to that of a report of T. spiralis in cougars in Argentina (Ribicich, et al, 2010, 1 lpg). The cougar in this work showed a better overall condition than the one described by Hidalgo et al (2013). Although the disease has been reported in animals (Rice, et al, 1990;Ribicich, et al, 2007;Bowman, 2009;Ribicich, et al, 2013), the infecting dose necessary for clinical signs is usually high, resulting in higher larvae densities than that observed in this report.…”
Section: Discussioncontrasting
confidence: 55%
“…There is no report of Trichinella in wild hosts other than in P. concolor in Chile (Álvarez, et al, 1970;González-Acuña, et al, 2010), and rats reported to host Trichinella larvae have been found only in association with human settlements (e. g. Poupin, 1897). Thus, in Chile, the cougar and the wild boar are the only species that represent any evidence of a possibly existing sylvatic cycle of Trichinella (García, et al, 2005;Hidalgo, et al, 2013). In contrast, in Argentina, Trichinella has been documented in wild boar (Cohen, et al, 2010), and it has also been found in the armadillo (Chaetophractus villosus), the central pericote (Graomys centralis), and in a species of fox (Lycalopex gymnocerus gracilis) (Minoprio, et al, 1967;Krivokapich, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[33] In Chile, human trichinosis is endemic and the rst indigenous cases were published more than a hundred years ago and its occurrence is closely related to cultural habits and diet. [34] T. spiralis has been found in domestic pigs, rats, cats, dogs and pumas [35], from which pigs and rats have a greater importance in domestic infection cycles. Domestic pigs usually eat infected rats, causing trichinellosis in humans by the ingestion of undercooked meat containing encysted larvae.…”
Section: Echinococcosismentioning
confidence: 99%